Relationship between appendicular muscular mass index and physical function in older people - Miguel Alarcón-Rivera; Carolina Cornejo-Mella; Camila Cáceres-Aravena; Yeny Concha-Cisternas; Paz Fernández-Valero; Eduardo Guzmán-Muñoz (AIMS Press, 2024)
This study aimed to establish the relationship between the appendicular muscle mass index (AMMI), assessed from anthropometric variables, and the physical function of older people. Seventy-six older people participated in this study (72.03 ± 7.03 years). The participants underwent evaluations to determine their AMMI using anthropometry (weight, calf circumference, hip circumference, and knee height) and manual grip strength. Additionally, their physical function was evaluated using the 5-chair stand test, the 3-meter walk test, and the timed up and go test (TUG) to determine the strength of the lower limbs, the gait speed, and the dynamic balance, respectively. The results show that the AMMI did not present a significant relationship with the 5-chair stand test in both women (r = -0.135; p = 0.204) and men (r = -0.067; p = 0.349). The AMMI was moderately correlated with the gait speed in both women (r = 0.542; p < 0.001) and men (r = 0.556; p < 0.001). Finally, a statistical significance was observed in the relationship between the AMMI and the TUG test in women (r = -0.273; p = 0.047) and older men evaluated in this study (r = -0.284; p = 0.042). In conclusion, there is a relationship between the AMMI and both the dynamic balance and the gait speed. Therefore, the AMMI emerges as a potential public health assessment by enabling the clinical quantification of muscle mass and an estimation of physical function in the elderly population.